The Effect of Transfer Pricing, Book Tax Difference and Thin Capitalization on Tax Avoidance Practices - Elishang, Rachelle; Fahmi, Muhammad; Kurniawan, Rudy (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2024)
The aim of the study is to test and examine the effect of transfer pricing, book tax difference and thin capitalization on tax avoidance practices. This study uses quantitative methods with a population in the form of all consumer goods industry entities listed on the IDX for the period 2021-2023. Secondary data is the data needed for research and is sourced from the IDX website. Purposive sampling was applied in order to obtain samples and produce a data sample of 72 samples which after trimming extreme data outliers became 63 samples. Data processing utilizes IBM SPSS Statistic 25 software and multiple regression analysis testing, The test results in this study reveal that simultaneously all transfer pricing, book tax difference and thin capitalization variables affect tax avoidance practices. The results in the partial test show that tax avoidance practices can be influenced by transfer pricing. Conversely, book tax difference and thin capitalization do not affect tax avoidance practices. This study has a sample data update of 2023 and examines a sector that is quite rarely researched in related variables. This research is expected to contribute to the understanding and insight of the literature in. In addition, this research is expected to contribute to increasing regulation and public awareness regarding tax avoidance practices also designing more effective tax policies.